Kelayakan dan Penerapan Artificial Intelligence (AI) sebagai Direktur Perusahaan - Yuda Darma Jaya; Muh. Jufri Ahmad (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research uncovers the implementation of AI in companies with a focus on feasibility and implementation aspects. Examines key challenges in implementing AI, including legal and ethical compliance, and provides possible solutions for safe and productive AI integration. The aim is to identify barriers, evaluate compliance, and offer guidance for the appropriate use of AI and in accordance with normative regulations (Normative Legal Research) or literature research. Normative research is legal research to discover legal rules, legal principles, by collecting legal materials, such as legal norms, legal rules, and legal principles which are then analyzed to produce a prescription regarding the problem formulation. The results of this research shows that AI can provide major benefits within the enterprise, but faces a number of regulatory challenges. Key findings involve expanding legal, ethical and data privacy compliance in implementing AI. Cooperation between companies, government and stakeholders is needed to create balanced regulations and support the safe and efficient use of AI. A revision of the Company Law is needed to clarify the role, authority, responsibilities, rights and obligations of artificial intelligence in company directors. Legal regulations need to specifically regulate how artificial intelligence providing commands will be held legally accountable, highlighting the urgency regarding accountability for AI actions that can have significant legal impacts.